Identified mental disorders in older adults in primary care: A cross-sectional database study. (1st January 2018) - McCombe, Geoff; Fogarty, Frank; Swan, Davina; Hannigan, Ailish; Fealy, Gerard M.; Kyne, Lorraine; Meagher, David; Cullen, Walter
Abstract: Introduction: Identifying and managing mental disorders among older adults is an important challenge for primary care in Europe. Electronic medical records (EMRs) offer considerable potential in this regard, although there is a paucity of data on their use for this purpose. Objectives: To examine the prevalence/treatment of identified mental disorders among older adults (over 55 years) by using data derived from EMRs in general practice. Methods: We utilized data from a cross-sectional study of mental disorders in primary care, which identified patients with mental disorders based on diagnostic coding and prescribed medicines. We collected anonymized data from 35 practices nationally from June 2014 to March 2015, and secondary analysis of this dataset examined the prevalence of mental disorders in adults aged over 55 years. Results: 74, 261 patients aged over 55 years were identified, of whom 14, 143 had a mental health disorder (prevalence rate of 19.1%). There was considerable variation between practices (range: 3.7–38.9%), with a median prevalence of 23.1%. Prevalence increased with age, from 14.8% at 55–59 years to 28.9% at 80–84 years. Most common disorders were depression (17.1%), panic/anxiety (11.3%), cognitive (5.6%), alcohol (3.8%) and substance use (3.8%). Conclusions: Examining mental disorders among older adults using data derived from EMRs is feasible. Mental disorders are common among older adults attending primary care and this study demonstrates the utility of electronic medical records in epidemiological studies of large populations in primary care.